Eleventh hour CISSP study guide - Conrad, Eric (Syngress eleventh hour series, 2014)
This study study guide is keyed directly to the most current version of the CISSP certification exam for information security professionals. Streamlined to include only core certification information and presented for ease of last-minute studying, it highlights key concepts covered on the exam.